A METHODICAL STUDY ON RATIONALE TO GREEN INITIATIVES OF IT COMPANIES AT TECHNOPARK, KERALA (International Journal of Food and Nutritional Sciences, 2022)
As the greenest IT Park in India, Technopark still strives to live up to its tag. The folks at Prakruthi, a green campus club celebrating its first anniversary, announce that some 30,000 seedlings of vegetables such as Brinjal, Okra, Runner Beans, Wide Beans, Red Amaranthus, Tomato, Chilli, and the like have been distributed to 670 techies themselves. In addition to this, with a first-of-its-kind integrated and decentralised waste treatment facility, Technopark is going green. Technopark companies are perceived as being environmentally conscious and aim to build a vision of treatment. Technopark’s businesses have demonstrated that renewable energy sources minimise energy demand and lower electricity bills. The most important rationale for the Green Initiatives of IT companies at Technopark, Kerala is owing to the Competitive Aspects, Profitability Aspects, Client Requirement Aspect, Legal and Regulatory Aspects, CSR Aspects. There is a difference in the Intrinsic and Extrinsic Aspects of Green Initiatives of IT companies at Technopark, Kerala.